(untitled) (Historia, 2021)
Samuel Elsevier (1653-1724), Secunde aan de Kaap de Goede Hoop van 1697 tot 1707 en geestverwant-medewerker van Willem Adriaan van der Stel, wordt in de geschiedschrijving traditioneel beschreven als een typische hoge Compagniesdienaar. Een hooghartig, hardvochtig, ambitieus, hebzuchtig en omkoopbaar man dus. Dat oor-deel is voor een deel gebaseerd op onvolledige, verouderde of verkeerd geïnterpre-teerde gegevens. Dat blijkt uit allerlei archivale gegevens hier voor het eerst bekend gemaakt. Deze gegevens dwingen de biografie van Samuel Elsevier op diverse punten te herzien. Samuel Elsevier (1653-1724), the senior official of the Dutch East India Company (DEIC) at the Cape in the period 1697 to 1707 closely associated with Willem Adriaan van der Stel, is traditionally perceived in historical writing as a typical senior company official. His temperament of arrogance, passion, ambition and greed syupposedly made him susceptible to corruption. It is a perception based on incomplete, dated or incorrectly interpreted details. It appears from all types of archival information, disclosed for the first time in this article. Tghe information has a bearing on his familial background, that of his wife, their respective life histories, the history of the family, his career, property and also slaves. In the light of new evidence the biographer is forced to revise the perception of Samual Elzevier in a number of respects.